THE DETERMINANTS OF DIGITAL BANKING ADOPTION AMONG BANKS OFFERING ISLAMIC BANKING SERVICES - Hidayat, Achmad; Kassim, Salina (Journal of Islamic Monetary Economics and Finance, 2023)
Technology advances in the financial sector have been a topic of much discussion within the banking industry. It is believed that the adoption of digital banking by banks depends greatly on their characteristics and the market they operate. This study examines the relationship between bank and market characteristics and the adoption of digital banking among banks that offer Islamic banking services in Indonesia. Data are gathered from banks’ annual reports, their first mobile banking app, financial reports, and banking statistics from 2010 to 2022. A panel logistic regression is utilized in the analysis. The results indicate that bank and market characteristics have a meaningful impact on a bank's decision to adopt digital banking. Additionally, it is found that banks are more inclined to adopt digital banking during the COVID-19 pandemic.